The Influence of Experiential Marketing and E-Service Quality on E-Satisfaction and Repurchase Intention - Ni Putu Nita Anggraini; I Wayan Gede Antok Setiawan Jodi; Dedik Pratama Putra (Journal of International Conference Proceedings (JICP), 2020)
This study aims to investigate the impact of experiential marketing and e-service quality on repurchase intention through e-satisfaction. Information assortment was directed utilizing purposive examination by disseminating to 100 respondents. The aftereffect of this examination demonstrates that : (1) experiential showcasing directly effects on e-satisfaction, (2) e-service quality directly effects on e-service quality, ((3) experiential marketing directly effects on repurchase intention, (4) e-service quality directly effects on repurchase intention, (5) e-satisfaction directly effects on repurchase intention, (6) e-satisfaction can mediate variables between experiential marketing with repurchase intention, (7) e-satisfaction can mediate variables between e-service quality with repurchase intention.